2019
DOI: 10.14814/phy2.14176
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning by aerobic exercise reduces acute ischemic renal injury in rats

Abstract: Acute kidney injury (AKI) can be defined as the sudden loss of renal function associated with structural changes in the kidneys. Currently, 13.3 million people die of AKI around the world. Normally aerobic exercise is used both as/for the treatment and prevention of high blood pressure, metabolic disease and Diabetes mellitus (DM). Nevertheless, exercise preconditioning must be a crucial resource in the prevention and mitigation of AKI. The aim of this study was to evaluate the effects of the exercise precondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
(41 reference statements)
3
20
0
Order By: Relevance
“…These biomarker data were corroborated by histological observations, where reduced severity of tubular injury [23] and reduced lymphonuclear infiltrates [24] were seen, indicating more advanced renal recovery in the exercise groups. The key mechanisms of exercise induced renal protection highlighted were autophagy [23] and anti-oxidative stress [24]. As mentioned, autophagy plays a key role in cellular homeostasis and is responsible for the degradation and reprocessing of intracellular components to either result in cell death or survival [56,57].…”
Section: Autophagy Upregulationsupporting
confidence: 62%
See 3 more Smart Citations
“…These biomarker data were corroborated by histological observations, where reduced severity of tubular injury [23] and reduced lymphonuclear infiltrates [24] were seen, indicating more advanced renal recovery in the exercise groups. The key mechanisms of exercise induced renal protection highlighted were autophagy [23] and anti-oxidative stress [24]. As mentioned, autophagy plays a key role in cellular homeostasis and is responsible for the degradation and reprocessing of intracellular components to either result in cell death or survival [56,57].…”
Section: Autophagy Upregulationsupporting
confidence: 62%
“…More therapeutic options to improve renal recovery after AKI are required [58]. Exercise has been effective in achieving this in animal studies [23][24][25][26][27][28][29] through its anti-inflammatory, anti-fibrotic, and anti-oxidative effects as well as through autophagy upregulation. At present, the promising results from animal studies have not been replicated in clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of AKI, physical exercise has been shown as a tool to improve clinical parameters ( Miyagi et al, 2014 ; Estrela et al, 2017 ). In 2019, de Lima et al (2019) showed that preconditioning by aerobic exercises reduces acute ischemic renal injury in rats. In another study, physical exercise has been shown to be able not only to decrease some kidney injury markers but also to diminish cisplatin-induced AKI ( Estrela et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%